Modernization of Education: a New Approach ‎and Method in Learning Islamic Religious ‎Education - Syamsul Aripin Syamsul Aripin; Nana Meily Nurdiansyah (TADRIS: Jurnal Pendidikan Islam, 2022)
The purpose of this study is to describe Islamic religious education as the main subject taught at various levels of educational units that are facing serious problems, namely the threat of modernization that changes all human life in various fields, including education, in the era of modernization education is required to be responsive in overcoming various problems. faced by humans, education is faced with the demands of modern humans who want education graduates to master various fields and expertise. This research is qualitative research using exploratory research. The data analysis technique used phenomenological analysis and data collection methods in this study using observation, in-depth interviews, and documentation studies. The results of this study need to reformulate the education system based on the needs of modern society, one of the strategic steps is to change the approach and learning method of Islamic religious education in schools from the old model to the new model and this effort has already been carried out by superior schools in Indonesia, especially by schools. Islamic Senior High School Al-Azhar 1 Jakarta in the field of PAI studies which has benchmarks of success and five approaches in learning Islamic Religious Education including the following approaches: first, experience; second, habituation; third, Emotional; fourth, Rational; and Fifth, Functional. As well as creating special methods for each material in the Islamic Religious Education curriculum. The methods of the material are: first, the method of teaching faith; second, worship; third, morality; fourth, the history of Islamic culture; Fifth, the Qur'an.